Is Nd:YAG laser effective for inhibiting the growth of Candida albicans and Candida tropicalis? - Hossein Malekzadeh; Mohammad Sabaeian; Mansour Amin; Akbar Abasnezhad; Fatemeh Babadi (Mashhad University of Medical Sciences, 2023)
Objective: Candida albicans and Candida tropicalis are the most common fungal species in humans. The present study aimed to investigate the effect of neodymium-doped yttrium aluminum garnet (Nd:YAG) laser on inhibiting the growth of Candida albicans and Candida tropicalis in vitro. Methods: Candida albicans and Candida tropicalis species were cultured in sub-dextrose agar containing chloramphenicol and exposed to Nd:YAG laser (1064 nm). The laser was emitted at the pulse frequency of 1 Hz (1 pulse per second) for 7 or 13 seconds. At each pulse duration, the energies of 40, 60, 80, or 100 mJ were delivered to microbial plates. After radiation, the number of colonies was counted and reported as colony-forming units per milliliter (CFU/mL). Results: There was a significant reduction in the number of Candida albicans and Candida tropicalis colonies after Nd:YAG laser radiation, compared to the control group (P<0.05). At the pulse duration of 7 seconds, there was a significant difference in the number of Candida albicans colonies between the pulse energy of 40 mJ with other pulse energies (P<0.05). At the pulse duration of 13 seconds, the energies of 80 mJ and 100 mJ were significantly more potent at killing Candida tropicalis than other pulse energies (P<0.05). Increasing the duration of irradiation from 7 to 13 seconds was effective at killing Candida species at most pulse energies (P<0.05). Conclusions: Nd:YAG laser is effective in inhibiting the growth of Candida species. Under the conditions of this study, the antifungal effect of Nd:YAG laser improved with increasing pulse energy and duration of laser irradiation. (J Dent Mater Tech 2023;12(2): (68-72)